Farm gate price determinants in small-scale maize production: A case study in Anuradhapura district - Dissanayake, D.M.W.P.; Koralagama, D.N.; Sandika, A. (Colombo : Sri Lanka Association for the Advancement of Science, 2021)
Maize (Zea mays) is the second largest cultivated crop apart from paddy in Sri Lanka. A significant price gap is noticeable between farm gate prices (FG) and retail prices of maize. This paper examines the price determinants influence on FG price of raw and dried maize produced by small scale maize (SSM) producers in Anuradhapura. A sample of 100 SSM farmers were selected using simple random sampling technique, from proportionately selected five divisional secretariat divisions (DSDs) in Anuradhapura district based on the highest production. Thus, the sample comprised with small- scale maize farmers from Galenbidunuwewa (27), Kebithigollewa (18), Thalawa (25), Kekirawa (13) and Thirappane (17). A questionnaire survey was administered for primary data collection considering the variables of marketing practices and production management factors. Secondary data of average FG prices of maize were obtained from Hector Kobbekaduwa Agrarian Research Institute. Data was analyzed using inferential (ANOVA) and descriptive statistics. The findings revealed that many farmers se l their harvest through multiple buyers including middlemen (19%), retailers (1%) and a majority is sold to both middlemen and retailers (80%). Buyers prefer to buy dried maize at high prices than raw maize. Highest FG prices were obtained via seed maize for agricultural purpose from type of market (p=0.000), transporting by lorry from transport mode (p=0.032) with highest storage availability (p=0.001), and stored mostly in houses (p=0.008). Full-aware (p=0.000), quality concerned (p= 0.001) maize farmers who were not used post-harvest methods (p=0.012) gained high FG prices. Quality management factors like seed color (p=0.000), moisture content of seeds (p=0.000), maturity level (p=0.000) and removing damages (p=0.000) influenced the FG price of maize. Quality improvement (92%), post harvest handling (74%), effectiveness of agronomic practices (89%), infrastructure facilities (97%), awareness programs (100%), input provisioning (100%) and agricultural extension services (97%) were requested for better quality production. Information dissemination and establishment of competitive markets were mostly affected for fair FG prices of SSM farmers in Anuradhapura district.
Keywords: Farm Gate Price; Maize Production; Maize Buyers; Price Determinants; Quality